2009
DOI: 10.3354/meps08003
|View full text |Cite
|
Sign up to set email alerts
|

Diel changes in humpback whale Megaptera novaeangliae feeding behavior in response to sand lance Ammodytes spp. behavior and distribution

Abstract: Humpback whales Megaptera novaeangliae have adopted unique feeding strategies to take advantage of behavioral changes in their prey. However, logistical constraints have largely limited ecological analyses of these interactions. Our objectives were to (1) link humpback whale feeding behaviors to concurrent measurements of prey using scientific echo-sounders, and (2) quantify how sand lance behavior influences the feeding behaviors and foraging ecology of humpback whales. To measure, in fine detail, the 3-dimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
111
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 113 publications
(117 citation statements)
references
References 32 publications
5
111
0
1
Order By: Relevance
“…Similarly, several studies found that blue whales Balaenoptera musculus in pelagic waters dove deeper during the day than at night, likely while foraging on krill (Croll et al 1998, Oleson et al 2007). Additionally, a diel pattern of deep night dives and shallow daytime dives was found for 2 associated Bryde's whales likely foraging on krill in pelagic waters in the eastern North Atlantic off Madeira Island (Alves et al 2010) and for humpback whales Megaptera novaeangliae likely foraging on sand lance (Ammodytidae) along the bottom at Stellwagen Bank in the western North Atlantic (Friedlaender et al 2009). Further tagging research is needed to increase the sample size and determine whether the documented dive behavior is representative of the GoM Bryde's whale population.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, several studies found that blue whales Balaenoptera musculus in pelagic waters dove deeper during the day than at night, likely while foraging on krill (Croll et al 1998, Oleson et al 2007). Additionally, a diel pattern of deep night dives and shallow daytime dives was found for 2 associated Bryde's whales likely foraging on krill in pelagic waters in the eastern North Atlantic off Madeira Island (Alves et al 2010) and for humpback whales Megaptera novaeangliae likely foraging on sand lance (Ammodytidae) along the bottom at Stellwagen Bank in the western North Atlantic (Friedlaender et al 2009). Further tagging research is needed to increase the sample size and determine whether the documented dive behavior is representative of the GoM Bryde's whale population.…”
Section: Discussionmentioning
confidence: 99%
“…Prior to deployment, the time on the tags was synchronised to the GPS time to ensure the ability to synchronise data parameters (e.g. Friedlaender et al 2009). …”
Section: Methodsmentioning
confidence: 99%
“…However, there is limited evidence that humpback whales feed at night using putative echolocation (Stimpert et al, 2007) or tactile mechanisms (Friedlaender et al, 2009). Crittercam deployments on blue whales show that daytime foraging dives often involve lunges at steep upward pitch angles [see fig.4 in Calambokidis et al ; cf.…”
Section: Theoretical Versus Observed Foraging Behaviormentioning
confidence: 99%
“…This lunge feeding behavior occurs anywhere prey is particularly dense and abundant, from the sea surface (Friedlaender et al, 2009) to more than 500m in depth (Panigada et al, 1999). During a single lunge, rorquals accelerate to high speed towards a prey patch (Friedlaender et al, 2009;Goldbogen et al, 2008;Goldbogen et al, 2006) and open their mouths wide to approximately 80deg (Brodie, 1993;Brodie, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation